San Jose del Monte General Hospital gardens in health care facilities, integrating sustainable design - Avisado, Mary Joy M.; De Leon, Ruby Teresa (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
This research seeks to analyze the importance and correlation between nature, people, and structure. The research focuses on having a new Public Health Care facility in San Jose del Monte that will integrate sustainable design with the concept of healing garden. This study will also present some ideas in designing with the consideration of its natural surroundings as well as the importance of it to the users, especially the patients. Some sustainable design ideas also will be discussed and the use of Green Roofing system as one of the sustainable ideas implemented. It will also give general information about designing. Type II hospital as well and present some guidelines that has been used in this study. With the concepts and informations gathered, this study will present the final design of the health care facility with plans and perspectives.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Health care facilities -- Design